Across the centuries: Piecing together the anatomy of the heart - Wallisa Roberts; Sonja Salandy; Gaurav Mandal; M.K. Holda; K.A. Tomaszewksi; Jerzy Gielecki; R. Shane Tubbs; Marios Loukas (Elsevier, 2019)
Background: The history of the cardiac anatomy dates back to 3500 B.C. when the Greeks and Egyptians based their understanding of this structure on their religious beliefs. During the 5th century, Hippocrates, the "Father of medicine," established medicine as a science and highlighted the principles of medical knowledge, replacing these previous tenets. Methods: This literature review seeks to collate and discuss peer-reviewed articles on the history of cardiac anatomy. Results: Advances in the understanding of the structure, location and function of the heart occurred during the post-Hippocratic era. Upon establishment of its anatomic structure, the interconnection between the heart and the lungs was sought and the pulmonary circulation was described. After the first description of the heart as a pump was made, it was followed by the innervation of the cardiac system, as well as a description of the conducting system in the eighteenth, nineteenth and twentieth centuries. Conclusion: The history of the cardiac anatomy was widely influenced by intellects of varying backgrounds, which led to significant contributions to our current understanding. Keywords: Anatomy, Anatomists, Heart, History, History of medicine, Humans